An Investigation into the Certainty of Provisions Based on Confession and Experts’ Consensual Judgments and Perspectives in Legal Lawsuits in Iranian Courts - Taram, Maysam; Parhammeh, Hamid Reza; Zeajeldi, Iman (Journal of History Culture and Art Research, 2017)
In legal disputes, in some cases which judges cannot issue verdict due to the specialty of the matter, an expert or more are assigned by court as requested by parties to issue verdict. Now this question arises is that can the verdict issued based on confession and experts’ perspectives be objected by parties? This study seeks an answer to this question by examining Civil Code and verdicts of Supreme Court as well as current literature.